Distillation Control, Optimization, and Tuning: Fundamentals and Strategies Fundamentals and Strategies - Robbins, Lanny (Taylor & Francis, 2011)
Emphasis on improved quality and performance of distilled products and the demand for reduced operating costs place a heavy burden on both the personnel responsible for profitability and the manufacturing department charged with operating the processing equipment. There have been dramatic improvements in the computer software and hardware used to simulate and model the distillation process and potential response to experimentation, but mastering the art of distillation process and control still requires solid understanding of a large body of information. With a focus on achieving product purity at low cost, Distillation Control, Optimization, and Tuning: Fundamentals and Strategies highlights core concepts. These include process variables for continuous binary distillation columns and the four basic control strategies, the distillate and bottoms product quality performance objectives, and the tuning of process control loops. Without dwelling on complex mathematical descriptions, the book presents the fundamentals of process control of a distillation column as a separation and purification unit operation. It covers the concepts and functional criteria that are critical to successful implementation of process control, as well as measurement and improvement of product quality performance. It describes how process control loops for distillation columns can be tuned for stable operation, with a balance between minimum variability from setpoint changes and excellent response to load disturbances. Designed for students, engineers, technicians, and plant operators alike, this book emphasizes the prevailing need to strike a balance between the details of hypotheses and good engineering judgment. The author outlines learning objectives at the beginning of each chapter and includes chapter-end summaries, exercises, and references to help readers acquire essential knowledge and understanding. The result is a resource that will inform future decisions for the design, operation, and troubleshooting of distillation process control systems.